The relationship between the timeliness of meal serving and patient food waste in the inpatient ward of Batu Bara regional general hospital - Winda Rizki Pebrina, Batubara; Agnes Yenni Situmorang; Wira Maria Ginting; Desri Meriahta; Monika Helen Sinaga (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Food service in hospitals is one of the indicators of nutrition service quality, where the timeliness of meal delivery and food waste are key concerns. This study aims to determine the relationship between meal delivery timeliness and food waste among inpatients at RSUD Batu Bara. The study employed a descriptive- analytic design with a cross-sectional approach, involving 36 respondents selected through quota non-random sampling. Timeliness data were collected through observation, while food waste was measured using a weighing method. The results showed that the average food waste was 16.52 %. The timeliness of meal delivery was considered moderate (61.1% on time) but did not meet the hospital standard of ≥90%. Pearson correlation analysis indicated no significant relationship between meal delivery timeliness and patient food waste (p > 0.05). In conclusion, although timely meal delivery is important, other factors appear to play a more dominant role in influencing patient food waste.